2001
DOI: 10.1128/jvi.75.22.10593-10602.2001
|View full text |Cite
|
Sign up to set email alerts
|

Simian Virus 40 Large-T-Antigen-Specific Rejection of mKSA Tumor Cells in BALB/c Mice Is Critically Dependent on both Strictly Tumor-Associated, Tumor-Specific CD8+Cytotoxic T Lymphocytes and CD4+T Helper Cells

Abstract: Protective immunity of BALB/c mice immunized with simian virus 40 (SV40) large T antigen (TAg) against SV40-transformed, TAg-expressing mKSA tumor cells is critically dependent on both CD8؉ and CD4 ؉ T lymphocytes. By depleting mice of T-cell subsets at different times before and after tumor challenge, we found that at all times, CD4 ؉ and CD8 ؉ cells both were equally important in establishing and maintaining a protective immune response. CD4؉ cells do not contribute to tumor eradication by directly lysing mK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…After injection of 10 6 mKSA cells, i.e. the ten-thousand-fold dose of tumor cells lethal for 50% of the mice [ 10 ], all naïve wtBALB/c mice (13/13 mice) succumbed to mKSA tumors within a mean survival time of 21 days (Table I ). Immunization by two sc injections of SV40 established long-term protection against mKSA tumors in almost all (12/13 mice) wt mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After injection of 10 6 mKSA cells, i.e. the ten-thousand-fold dose of tumor cells lethal for 50% of the mice [ 10 ], all naïve wtBALB/c mice (13/13 mice) succumbed to mKSA tumors within a mean survival time of 21 days (Table I ). Immunization by two sc injections of SV40 established long-term protection against mKSA tumors in almost all (12/13 mice) wt mice.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, protective cellular immunity against transplantable murine SV40 tumors can be achieved by pre-immunization with SV40 or purified T-Ag, which induces an efficient and long-lasting CD4 + helper T-cell dependent CTL response against established SV40 tumor cells (e.g. mKSA) [ 9 , 10 ]. As the T-Ag specific CTL response in BALB/c mice is weak, and as, furthermore, the major histocompatibility complex (MHC) class I H-2 d restricted T-Ag specific T-cell epitopes have not yet been characterized, the analysis of T-Ag specific CD8 + T-cell responses in BALB/c mice is technically difficult.…”
Section: Introductionmentioning
confidence: 99%
“…with mKSA tumor cells (40). During the course of immunization and tumor cell challenge (i.e., the induction and effector phases), both CD4 ϩ and CD8 ϩ T-cell subsets were found to be required immunologic components to achieve protection from mKSA cell tumorigenic growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for CD8 ϩ T-cell activity against SV40 Tagexpressing mKSA tumor cells after recombinant SV40 Tag protein immunization has been reported previously (1,40,47). However, this is the first report detailing the requirement of CTL activity after the onset of mKSA tumor cell challenge (i.e., the effector-phase response) in an experimental pulmonary metastasis model.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to in vivo studies on the mechanism(s) of recombinant SV40 TagÀinduced immunity in murine tumor models, we are still of the opinion that antibodies and CD4 T cells share either a dual or interdependent role. Recently, studies using a different recombinant SV40 Tag preparation, the solid tumor model, and in vivo depletion of CD4 and CD8 cells, suggested that CD8 CTL are critical in SV40 TagÀinduced immunity and that the activation of these effector cells by CD4 T helper cells is the mechanism by which CTLs target the tumor cell [70]. Previously, these investigators proposed that CD8 T cells are the major effector mechanism and are required for tumor immunity in BALB=c mice induced by recombinant SV40 protein strategies [71].…”
Section: Future Studies To Clarify the Role Of Antibodies And Cd4 T Cmentioning
confidence: 99%